Synthesis of sodium alginate/phosphorus tetramethylmethyl sulfate biocomposite beads with exceptional adsorption rate for Cr(VI) removal. Issue 2 (April 2023) - Liang, Shuling; Cai, Weiquan; Dang, Chengxiong; Peng, Xiong; Luo, Zhijia; Wei, Xingchuan
Abstract: Sodium alginate/phosphorus tetramethylmethyl sulfate beads (SAB-THPS) with diameters of about 2–5 mm and super-fast adsorption rate for Cr(VI) removal were successfully prepared by impregnation at 25 °C to crosslink phosphate groups on the surfaces of sodium alginate beads (SAB) using bis[tetrakis(hydroxymethyl)phosphonium] (THPS) as the modifier. The static adsorption of SAB-THPS conforms to the pseudo-second order kinetics and Langmuir model on monolayer chemical absorption; its maximum adsorption capacity fitted from Langmuir model is 145.77 mg/g, which is much higher than that of SAB (21.51 mg/g). Especially, SAB-THPS shows ultra-fast adsorption rate below initial Cr(VI) concentrations of 100 mg/L; it achieved removal efficiencies of more than 99.7 % at 2.5, 6.5 and 20 min, respectively with initial Cr(VI) concentrations of 20, 50 and 100 mg/L, respectively.Its adsorption mechanisms include main chemical reduction of Cr(VI) into Cr(Ⅲ), ions exchange and electrostatic interaction. The environmentally friendly SAB-THPS with the advantages of ultra-fast adsorption rate, high adsorption capacity and easy separation shows good application prospect for rapid remediation of wastewater. Graphical Abstract: Sodium alginate/phosphorus tetramethylmethyl sulfate biocomposite beads (SAB-THPS) with diameters of about 2–5 mm and super-fast adsorption rate for Cr(VI) removal were successfully prepared by impregnation at room temperature to crosslink phosphate groups on the surfaces of sodium alginate beads using bis[tetrakis(hydroxymethyl)phosphonium] as the modifier. It can achieve the removal efficiencies of more than 99.7% at 2.5 min, 6.5 min and 20.0 min, respectively with the initial Cr(VI) concentrations of 20 mg/L, 50 mg/L and 100 mg/, respectively. ga1 Highlights: Synthesis of sodium alginate/phosphorus tetramethylmethyl sulfate beads (SAB-THPS). SAB-THPS from bis[tetrakis(hydroxymethyl)phosphonium] via impregnation at 25 °C. Proposition a new phosphoric acid modifier for sodium alginate. SAB-THPS shows super-fast adsorption rate for Cr(VI) removal than SAB beads. The adsorption mechanism mainly involves reduction of Cr(VI) into Cr(Ⅲ).